PEMETAAN INDEKS TINGKAT PELAYANAN JALAN PONOKAWAN SAMPAI JALAN MAYJEN BAMBANG YUWONO KRIAN KABUPATEN SIDOARJO DENGAN METODE LINIER - Sarra Amanda Sinaga; Siti Zainab; Hendrata Wibisana (Universitas Kristen Maranatha, 2021)
The development of West Sidoarjo especially at Krian city has a major influence on the growth of suburban areas. By increasing the number and activity of the population, transportation is one of the principal parts that cannot be separated from the activity. This leads to quite complex traffic problems, especially traffic density problems. This research was conducted to analyze the Service Level Index (ITP) with linear regression method on Jalan Ponokawan until Jalan Mayjend Bambang Yuwono Krian. The survey was conducted in the morning (07.00-09.00), afternoon (12.00-14.00), and evening (16.00-18.00) to analyze the calculation of traffic volume, road capacity, and the speed of the free flow by using Manual Kapasitas Jalan Indonesia (MKJI) 1997. The Geographic Information System (GIS) can help to provide information on road service level index analysis in the form of thematic maps that are easy to understand. From the results of data analysis, a service level index (a) is calculated on each segment using linear regression method and the result of segment I is 0,093, segment II is 0.141, segment III is 0.074, segment IV is 0.210, segment V is 0.130, segment VI is 0.109, and segment VII is 0.113.